1985
DOI: 10.1111/j.1469-7610.1985.tb01632.x
|View full text |Cite
|
Sign up to set email alerts
|

On Data Limitations in Hyperactivity

Abstract: Three groups of children rated firstly as overactive and distractible, secondly as distractible and thirdly as low on both activity and distractibility were examined in a visual search task with three levels of display load: two, three and four items. The children were tested twice in two conditions of stimulus visibility to examine the encoding stage of the model used here. The experimental results reject the hypothesis that an encoding deficit or data limitation may explain the attentional performance of eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
60
1
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 39 publications
7
60
1
1
Order By: Relevance
“…Example saccades of a boy with ADHD, a non-affected brother and a control boy on a 3-second delay trial of the memory-guided saccade task illustrating group differences for the tendency to under-versus overshoot the memorized target location Familial deficits in memory-guided saccades in ADHD lings (Leigh and Kennard 2004) 1 . This is also consistent with findings in visual search tasks of ADHD children and controls (Sergeant and Scholten 1985).…”
Section: Visuo-spatial Working Memorysupporting
confidence: 81%
“…Example saccades of a boy with ADHD, a non-affected brother and a control boy on a 3-second delay trial of the memory-guided saccade task illustrating group differences for the tendency to under-versus overshoot the memorized target location Familial deficits in memory-guided saccades in ADHD lings (Leigh and Kennard 2004) 1 . This is also consistent with findings in visual search tasks of ADHD children and controls (Sergeant and Scholten 1985).…”
Section: Visuo-spatial Working Memorysupporting
confidence: 81%
“…Research has revealed that this dysfunction originates in the processing stage involved in generating motor responses (Sergeant, 2005;Sergeant and Scholten, 1985). Event-rate (i.e., the speed at which stimuli are presented) varies the rate at which motor responses are required, making it an appropriate manipulation of energetic state (Sanders, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously demonstrated that ADHD patients (and impulsive adults) might trade accuracy for speed (Barkley 1990;Dickman and Meyer 1988;Sergeant and Scholten 1985;Sonuga-Barke et al 1996). Strictly speaking, such results do not indicate a process deficit in ADHD patients, but may reflect difficulties in the maintenance of an effective response set, aversion to delay, deficits in response inhibition, or differences in speed accuracy trade-off (Sonuga-Barke 2002).…”
mentioning
confidence: 97%